The Impact of Nickel Mining Activities on Watershed Hydrology and Coastal Sedimentation - Efrianto Efrianto; Muhammad Chaerul; Ismail Marzuki; Natsar Desi; Mahmud Mahmud; Eris Nur Dirman (Journal La Lifesci, 2026)
growing rapidly and have the potential to put pressure on the hydrological system of the Watershed (DAS) and the dynamics of sedimentation in coastal areas. The applied open-pit mining system causes extensive land clearing and reduced vegetation cover, which can increase surface runoff and soil erosion. This study aims to analyze the spatial relationship between nickel mining land clearing, watershed hydrological response, and coastal sedimentation levels during the period 2016–2025. The data used are multi- temporal Sentinel-2 Level-2A satellite images analyzed using the Normalized Difference Vegetation Index (NDVI) to identify the condition of mining land clearing and the Normalized Difference Turbidity Index (NDTI) to represent the level of sedimentation and turbidity of coastal waters. Spatial analysis was carried out based on watershed units to examine the upstream–downstream relationship between the intensity of mining land clearing and sedimentation responses in the estuarine zone. The results show that watersheds with a dominant low NDVI value tend to experience increased surface runoff and potential soil erosion, which in turn contributes to increased coastal sedimentation as indicated by relatively high NDTI values. These findings confirm a strong link between land cover changes due to nickel mining activities, watershed hydrological responses, and coastal sedimentation intensity. This research emphasizes the importance of a watershed-based approach in nickel mining environmental management and sedimentation impact mitigation efforts to maintain the sustainability of coastal ecosystems.